The Border between War and Peace. Power and Propaganda in Neo-Assyrian and Achaemenid Art - Castelluccia, Manuel (Actual Problems of Theory and History of Art, 2019)
This contribution aims to explore the concept of universal rule in Assyrian and Persian imperial art. The notion of world empire began in the Ancient Near East; the Neo-Assyrian and Achaemenid empires can be considered as the first real political powers which laid claims to universal hegemony through complex systems of political propaganda, based on writings, and monumental art and architecture. Assyrian political propaganda was a deliberate broadcast of violence displayed by a combination of visual art and royal inscriptions. The core idea was the invulnerability of the Assyrian king, his army and their will to overcome both natural and human obstacles. Emphasis was on the strong relationship between Assyria and its gods as opposed to the futile resistance of its enemies. Persian state propaganda, on the contrary, reflects the idea of a large multi-cultural empire based on voluntary submission and integration. Although its artistic perspective was mainly based on a typical Mesopotamian background, Persian royal art mostly did not employ narrative schemes, either in texts or images. Violence was not represented, and wars avoided. Achaemenid art shows a universal peaceful order based on the king’s tutelage.